POTRET PERILAKU DAN STRATEGI PEREMPUAN BURUH PERKEBUNAN DALAM MERESPONS KEMISKINAN (STUDI KASUS DI PTPN X AJUNG KABUPATEN JEMBER) - A. Erna Rochiyati Sudarmaningtyas (Faculty of Humanities, Jember University, 2012)
Differences in ethnic background do not lead to the different behavior patterns and strategies of the female plantation workers of the PTPN X Ajung, Jember regency. This is due to their similarities in low education level, early marriage ages and they have no sufficient life skills, play dual and even multiple roles, main income earners for their families. However, they do not identify themselves as poor people because of relying not merely on plantation sector, but also doing alternative jobs in work in informal sector. Keywords: behavior, female workers, plantation, strategy.